My Zdes . Here We Are - Vojtek, Jaroslav (Homolka, Mario ; Corba, David, 2005)
Duration: 01:16:00 After World War II, the Krnáč family moved from Central Slovakia to Sub-Carpathian Ukraine. After the territory came under Soviet rule, the family was forced to settle in Balgarka, a village in the Kazakhstan steppe, where they spent over forty years. After the break-up of the USSR, the family decided to leave Kazakhstan. In 2000, they sell the family house and set out on a journey to Slovakia, a country they know only from their parents´ stories. Their first attempts to find jobs and accommodation in Bratislava are not very successful. Looking for a place to settle they cross the country from east to west, but find only half-abandoned villages, closed factories and high unemployment. After a long quest, they settle down in the countryside. The parents start working on a local farm and the children enter high school. This new beginning is hard for all of them: the older family members feel uprooted and keep thinking of their lives back in Kazakhstan, the younger ones struggle to study and be accepted as equals. Filmed over a period of four years, the film is a warm personal portrait of multi-generational search for roots and for the future.